2005
DOI: 10.1158/0008-5472.can-05-0662
|View full text |Cite
|
Sign up to set email alerts
|

Penetratin Improves Tumor Retention of Single-Chain Antibodies: A Novel Step toward Optimization of Radioimmunotherapy of Solid Tumors

Abstract: Single-chain Fv (scFv) antibody fragments exhibit improved pharmacokinetics and biodistribution compared with intact IgG. The tumor uptake of scFvs is rapid, and the serum half-life is shorter than IgG. However, scFvs exhibit lower net dose deposition in the tumor due to a shorter residence time that limits their use in radioimmunotherapy. To improve the tumor uptake and retention of scFvs, we investigated the utility of cell-penetrating peptides, penetratin and transactivator of transcription (TAT). Biodistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 27 publications
(43 reference statements)
2
55
0
Order By: Relevance
“…This study revealed that the higher the number of CPP copies grafted on a cell-specific monoclonal antibody (Mab), the lower was the specificity of the Mab for the native cell. Significant localization and retention of CPP-Mab fragments in non-targeted tissues in vivo have been confirmed more recently by Jain et al, especially with a high peptide to antibody ratio [19]. In this study, the cell-penetrating "driving force" predominated over the specific antigen binding of the Mab fragments.…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivosupporting
confidence: 70%
See 3 more Smart Citations
“…This study revealed that the higher the number of CPP copies grafted on a cell-specific monoclonal antibody (Mab), the lower was the specificity of the Mab for the native cell. Significant localization and retention of CPP-Mab fragments in non-targeted tissues in vivo have been confirmed more recently by Jain et al, especially with a high peptide to antibody ratio [19]. In this study, the cell-penetrating "driving force" predominated over the specific antigen binding of the Mab fragments.…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivosupporting
confidence: 70%
“…In another study, Tat or Antennapedia peptides were co-administrated with sc(Fv) 2 fragments [19]. In such a situation, there was no stable link between the CPPs and the sc(Fv) 2 fragment.…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Many other cationic and hydrophobic cell penetrating peptides (CPPs) have been reported to perform intracellular delivery of proteins into cultured cells [22] , as well as in vivo delivery of enzymes such as galactosidase and Cre recombinase to tissues [23,24] . Also CPPs significantly enhanced retention of the antibody by tumors [25] . More importantly, most CPPs are nontoxic when used at low doses [26] .…”
Section: Introductionmentioning
confidence: 94%